Dietary total antioxidant capacity and risk of ulcerative colitis: A case‐control study. Issue 12 (14th November 2019) - Rahmani, Jamal; Kord‐Varkaneh, Hamed; Ryan, Paul M.; Rashvand, Samaneh; Clark, Cain; Day, Andrew S.; Hekmatdoost, Azita
Abstract : Objective: Data on the association between the antioxidant capacity of a diet and the risk of ulcerative colitis (UC) are scarce. This study aimed to assess whether a relationship exists between dietary total antioxidant capacity (TAC) and the odds of UC in Iranian adults. Methods: In this case‐control study, patients with UC and age‐matched healthy controls were recruited from a hospital clinic. All participants completed a validated 168‐item food frequency questionnaire, the results of which were subsequently used to generate dietary TAC. Ferric reducing‐antioxidant power values were used to calculate dietary TAC. Results: Altogether 62 patients with UC and 124 healthy controls were enrolled. UC patients had a higher calorific intake ( P < 0.01), and consumed more monounsaturated fatty acids ( P < 0.01), vitamin B9 ( P < 0.01) and calcium ( P = 0.02) compared with healthy controls, while the control group had a higher vitamin C intake than the participants with UC ( P < 0.01). In a fully adjusted model, participants who were in the highest quartile of dietary TAC had a lower risk of UC (odds ratio 0.11, 95% confidence interval 0.01‐0.73). Conclusions: A higher dietary TAC score was associated with lower odds of UC in this case‐control study. Further elucidation of the role of key dietary elements is now warranted.